THE EFFECT OF LEARNING STRATEGY AND READING INTEREST TO THE READING UNDERSTANDING ABILITY OF STUDENTS OF IAIN BUKIT TINGGI - Reflinda Reflinda Reflinda (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
Abstract, This study aims to determine the influence of learning strategies and reading interest on the ability of reading comprehension of IAIN Bukittinggi students. The question posed is: Whether the discoveri learning strategy associated with learning interests is better than expository learning. The research population is a 5th semester student at the Department of Religious Education at IAIN Bukittinggi. Samples are taken in two classes where one class is taught by a discoveri strategy and the other is taught by an expository strategy. Data were analyzed by using t test (different test). The results show that discover learning strategies in high interest groups and low interest have higher learning outcomes than classes taught with expository strategies.Keywords: Learning Strategy, Discovery, Ekspository, Learning Interest